IEEE PES ISGT Europe 2013 2013
DOI: 10.1109/isgteurope.2013.6695387
|View full text |Cite
|
Sign up to set email alerts
|

An end-user perspective on smart home energy systems in the PowerMatching City demonstration project

Abstract: In discussions on smart grids, it is often stated that residential end-users will play a more active role in the management of the electric power system. Experience in practice on how to empower end-users for such a role is however limited. This paper presents a field study in the first phase of the PowerMatching City project in which twenty-two households were equipped with demand-response-enabled heating systems and white goods. Although end-users were satisfied with the degree of living comfort afforded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Additionally, there might be a bias in user behavior and the activation frequency of the appliances due to the Hawthorne effect (see [39]). More multidisciplinary studies as mentioned in [12] on the subject are needed, especially regarding user behaviors [40][41][42].…”
Section: Flexibility and Smart Washing Machine And Dishwashermentioning
confidence: 99%
“…Additionally, there might be a bias in user behavior and the activation frequency of the appliances due to the Hawthorne effect (see [39]). More multidisciplinary studies as mentioned in [12] on the subject are needed, especially regarding user behaviors [40][41][42].…”
Section: Flexibility and Smart Washing Machine And Dishwashermentioning
confidence: 99%
“…Furthermore, based on the papers that focused on user experiences, with special attention paid to demand side management, it appears that the issue of the acceptance of smart grids is widely discussed. Only a few studies built on evaluations of real life experiences based on smart grid projects [39,40], whilst most studies focused on future scenarios and (online) surveys [32,[40][41][42] (see report [43] for further details).…”
Section: Stakeholders Layermentioning
confidence: 99%
“…Stakeholders interact with smart grids through an interest or concern. Some features of smart grids, such as demand side management (DSM) and exchange of energy with other end users (peer-to-peer trading) involve individual end-user type stakeholders of the type of individual end users, whereas other features-such as a high penetration of renewable energy at a local level, as well as electric mobility [2,[4][5][6]-involve stakeholders of a more organizational character such as network operators and governmental organizations.…”
Section: Stakeholders Layermentioning
confidence: 99%
“…Looking at the stakeholders layer, the main focus is on residential customers and prosumers [31][32][33]. It was found that users, as they are described in the more recent research, not only have different labels-such as customers, consumers, prosumers and end users-but are also assumed to behave differently from each other [4,[34][35][36]. The most prevalent type reported on in the literature is the consumer, who is supposed to adapt to new developments in the energy system, such as smart grids.…”
Section: Stakeholders Layermentioning
confidence: 99%
See 1 more Smart Citation